2019
DOI: 10.1080/21691401.2019.1614594
|View full text |Cite
|
Sign up to set email alerts
|

A new method for early detection of pancreatic cancer biomarkers: detection of microRNAs by nanochannels

Abstract: Objective: To develop an effective new method for early detection of pancreatic cancer biomarkers and to aid early clinical diagnosis. Methods: A DNA probe (Probe) capable of specifically recognizing the target miRNA was designed. The specific probe of miRNA 21 is designed first, and then mixed with the miRNA 21 sample to form a complex molecule, and the complex molecule is added to the nanochannels to detect the received signal. The probe is designed to detect the electrical signal by means of pre-matching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The 5-year survival rate of patients with pancreatic cancer is less than 8%, and the average survival rate is less than 6 months. Considering that the mortality rate has been high in the recent decades, there is an urgent need to find effective biomarkers to promote and evaluate the diagnosis, treatment, and prognosis of pancreatic cancer [16][17][18]. The immune response in the microenvironment plays a decisive role in the progression, metastasis, and recurrence of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of patients with pancreatic cancer is less than 8%, and the average survival rate is less than 6 months. Considering that the mortality rate has been high in the recent decades, there is an urgent need to find effective biomarkers to promote and evaluate the diagnosis, treatment, and prognosis of pancreatic cancer [16][17][18]. The immune response in the microenvironment plays a decisive role in the progression, metastasis, and recurrence of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The profiles of miRNAs express visible difference in tumor and normal tissues of the patients, and regulation on the expression of special miRNAs has been thought as a feasible therapeutic strategy for cancer [ 16 , 17 ]. For instance, one study has found that miR-34a was significantly overexpressed in colon cancer cell, and downregulated miR-34a could promote the metastasis for the cells and poor prognosis for the patients, which is analogical with the observation from the previous study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of patients with pancreatic cancer is less than 8%, and the average survival rate is less than 6 months. Considering that the mortality rate has been high in the recent decades, there is an urgent need to nd effective biomarkers to promote and evaluate the diagnosis, treatment, and prognosis of pancreatic cancer [15][16][17] . The immune response in the microenvironment plays a decisive role in the progression, metastasis, and recurrence of tumors.…”
Section: Discussionmentioning
confidence: 99%